Experimentally induced mononucleosis-like heterophile antibodies in man - Leikola, J. (1969)
Nine human volunteers were immunized with sheep erythrocytes. In each of them, a small proportion of the antibodies formed after the primary stimulation resembled the heterophile mononucleosis antibody: they agglutinated sheep, horse and papain-treated ox red cells; their antigenic receptors on sheep and horse red cells were papain-sensitive; they were absorbable with ox red cells but not with guinea-pig kidney; they were macroglobulins. No corresponding antibodies were found in rabbit or guinea-pig immune sera. The observations suggest that the mononucleosis receptor on sheep red cells is immunogenic for man and that the heterophile antibody thus would be formed as a result of a distinct immunogenic stimulus.